(untitled) (Research, Society and Development, 2020)
The cultivation of sunflower (Helianthus annuus L.) in the second off-season, in the Brazilian Midwest region is an important economic and ecological strategy for the production system, whose knowledge of its water and nutritional needs is indispensable, due to the climate conditions at this time of year. The objective of the present study was to evaluate the growth and development of sunflower cultivation grown under different water deficit conditions and fertilizer levels with mineral and organomineral NPK. The experiment was conducted in plastic vases filled with dystrophic Red Latosol, located in an experimental area of the Federal Goiano Institute, in the municipality of Rio Verde, Goiás. The experimental design used was the randomized blocks analyzed in a 4 × 4 × 2 factorial scheme, with three repetitions. The treatments were the combinations of four water replacements equal to 50, 75, 100 and 125% of the available water capacity in the soil; four doses of the formulated NPK referring to 50, 100, 150 and 200% of the recommendation and two sources of the formulated NPK, mineral and organomineral. Water replacements were determined using electronic weighing lysimeters and water applied via a surface drip system. The increase in water replacement provides the highest plant height and stem diameter. The water replenishment of 125 and 103% provided the largest accumulation of dry matter of the leaves and stem, of the sunflower culture. At a dosage of 50% of the NPK recommendation, the organomineral source was superior to the mineral, for the dry mass of the leaves and fresh mass of the stem.